Al Azhar Hamka Islamic Education Institute: Past, Present, and Future - Selvia, Noor Liyana; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to examine the dynamics of the Al-Azhar Hamka Islamic educational institution, past, present, and future. This research was written based on a literature review and in-depth understanding and accumulated understanding from various trusted primary book sources. This research type is qualitative with a library research approach. Data collection techniques are carried out with documentation. Sources of data come from books and journals. Data analysis technique using Content Analysis. The study results show that Hamka's Thought in Al-Azhar is actually very centered on instilling values, ethics, and respect for nationalism as an important part of education. Without these three elements, Hamka sees that education is not yet a complete system. These three things are then elaborated in the spirit of Islam as well as Islamic values and the cultural heritage of science, language, and literature from Islamic civilization. Educational management from Al Azhar and Hamka must eventually learn to apply the values needed for modern education. The system used is no longer a top-down system but an engagement study and continued with the implementation of activities that are appropriate for existing students.